2015
DOI: 10.3748/wjg.v21.i5.1518
|View full text |Cite
|
Sign up to set email alerts
|

CNP signal pathway up-regulated in rectum of depressed rats and the interventional effect of Xiaoyaosan

Abstract: The CNP/NPR-B pathway is upregulated in the rectum of depressed rats and may be one mechanism for depression-associated digestive disorders. XYS antagonizes this pathway at least partially.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…These observations suggest that Xiaoyaosan may exert its pharmacological effect by regulating NES1 signals from the periphery. Although the mechanism of this pharmacological effect remains unclear, several studies have shown that Xiaoyaosan improves depressive-like behavior through the modulation of peripheral organs, for instance, the liver (39) and the intestine (28,40). Additionally, Xiaoyaosan downregulated the CIS-induced overexpression of OT, POMC, and MC4R in the rat hypothalamus.…”
Section: Discussionmentioning
confidence: 99%
“…These observations suggest that Xiaoyaosan may exert its pharmacological effect by regulating NES1 signals from the periphery. Although the mechanism of this pharmacological effect remains unclear, several studies have shown that Xiaoyaosan improves depressive-like behavior through the modulation of peripheral organs, for instance, the liver (39) and the intestine (28,40). Additionally, Xiaoyaosan downregulated the CIS-induced overexpression of OT, POMC, and MC4R in the rat hypothalamus.…”
Section: Discussionmentioning
confidence: 99%
“… 97 Another study found that the CNP–NPR2 pathway is upregulated in the rectum of rat models of depression; XYS partially antagonizes this pathway by inhibiting rectal tissue expression of CNP and NPR2. 103 …”
Section: Resultsmentioning
confidence: 99%
“…[ 20 , 25 ] CNP signals its activity via three types of natriuretic peptide receptors (particularly, NPR-B and NPR-C). Our previous study has shown that the CNP/NPR-B signal pathway is up-regulated in the rectum of depressed rats[ 1 ]. However, it is still unclear whether the NP/NPR signaling pathway changes or whether there is a relationship between depletion of ICC and changes in the natriuretic peptide signaling pathway in the stomachs of depressed rats.…”
Section: Discussionmentioning
confidence: 99%
“…Rats were maintained under previously described conditions for 1 week before they were subjected to the experiments. On the basis of the previous research methods, group M were singly housed and received one of the chronic mild unpredictable irritations daily: restraint, swim induced fatigue, footshock, fasting and concussion[ 1 ]. This study was performed with the approval of the Animal Ethics Committee of Dalian Medical University and all the experiments were performed according to the Guideline for the Care and Use of Laboratory Animals published by the Science and Technology Commission of the People’s Republic of China (STCC Publication No.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation